Aplicativos educacionais como apoio da alfabetização no ensino fundamental - LOBATO, Samara Oliveira (Instituto Federal do Amapá, 2021)
This article proposes to discuss the use of two literacy applications on mobile devices, namely: ABCD forming words and BINI abc, which helps teachers in the literacy process, but was specifically used in times of school reinforcement for the alpha class 1 that was created with students who are out of the age / grade and with learning difficulties, in order to innovate classes and improve student performance in reinforcement, the applications are very colorful and attractive, stimulate motor coordination, imagination , attention and phonological awareness